A new Literary Theory in Kurdish and Arabic Literature Based on Sheikh Nouri Sheikh Saleh and Nazek Almalaeka's Ideas - Pashabadi, Yadollah (Al-Adab Journal, 2021)
Sheikh Nouri Sheikh Saleh and Nazek Almalaeka, two prominent pioneer figures of Kurdish and Arabic literary renovation who have turned out as authorities, are originally from Iraqi Kurdish and Arabic backgrounds. Thanks to their works and activities, a novel literary theory came into being which led to emergence of a renaissance. Some of major concerns and questions posed by these two in their theory are measure, rhyme, poetic language, poem and society, and so on. This study, aside from the above-mentioned issues, adopts a descriptive-analytic method to deal with the role and status of these two experts in modern Kurdish and Arabic literature, their state of being pioneer, and the principles of their literary theory. Based on some of the findings of this study, there are some common and contrastive points of these two modernist authority in terms of their thoughts, attitudes, and viewpoints and certainly they have proposed some points in some specific regards.